Regulation of the BamHI restriction-modification system by a small intergenic open reading frame, bamHIC, in both Escherichia coli and Bacillus subtilis. - Ives, C L (1992)
BamHI, from Bacillus amyloliquefaciens H, is a type II restriction-modification system recognizing and cleaving the sequence G--GATCC. The BamHI restriction-modification system contains divergently transcribed endonuclease and methylase genes along with a small open reading frame oriented in the direction of the endonuclease gene. The small open reading frame has been designated bamHIC (for BamHI controlling element). It acts as both a positive activator of endonuclease expression and a negative repressor of methylase expression of BamHI clones in Escherichia coli. Methylase activity increased 15-fold and endonuclease activity decreased 100-fold when bamHIC was inactivated. The normal levels of activity for both methylase and endonuclease were restored by supplying bamHIC in trans. The BamHI restriction-modification system was transferred into Bacillus subtilis, where bamHIC also regulated endonuclease expression when present on multicopy plasmid vectors or integrated into the chromosome. In B. subtilis, disruption of bamHIC caused at least a 1,000-fold decrease in endonuclease activity; activity was partially restored by supplying bamHIC in trans.